2023
DOI: 10.1002/smll.202207619
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Stabilized Vanadyl Phosphate Monohydrate Ultrathin Nanosheets toward High Voltage Al‐Ion Batteries

Abstract: storage system, which would propel the substantial development of the energy storage technology. [4] In order to design high energy density storage devices, the identifying of host materials with high performance, especially elevated work potential, is essential. Due to the high electronegativity of oxygen, the metal oxides own strong ionic chemical bonds, which consequently result in increased plateau voltages. [5] Examples of such oxides owning potential high discharge voltages are amorphous V 2 O 5 (≈0.9 V)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 68 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…20 The diffraction peaks of typical layered structures were successfully detected, which is seen from the diffraction angles at 11.89 and 23.94, corresponding to the (001) and (002) peaks, respectively. 21 Interestingly, a slight shift of the peaks can be obviously observed when compared with those of VOPO 4 ·2H 2 O, which indicates that B has been doped into the layered structure. The XRD pattern of the local amplified area is displayed in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…20 The diffraction peaks of typical layered structures were successfully detected, which is seen from the diffraction angles at 11.89 and 23.94, corresponding to the (001) and (002) peaks, respectively. 21 Interestingly, a slight shift of the peaks can be obviously observed when compared with those of VOPO 4 ·2H 2 O, which indicates that B has been doped into the layered structure. The XRD pattern of the local amplified area is displayed in Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Mott-Schottky (impedance potential) measurements also showed that the electronic conductivity was greatly improved due to high concentration of O vacancies, which increases the carrier concentration by about 57 times [Figure 11B]. As a result of these unique characteristics, the specific capacity was 313.6 mAh g -1 at 0.1 A g -1 , and the retention was 76.8% after 500 cycles at 5.0 A g -1 [61] . Intercalation of aniline significantly increased the hydrophobicity of VOPO 4 •2H 2 O cathode, thus inhibiting dissolution.…”
Section: Zn-ion Batteriesmentioning
confidence: 99%
“…VOPO 4 displays a typical layered crystal structure with vertexsharing VO 6 octahedra and PO 4 tetrahedra in a 1:1 ratio [Figure 3F] [60] . Hydrothermal synthesized VOPO 4 tends to form the hydrate VOPO 4 •nH 2 O, which easily decomposes into VO x during cycling, so the cycling performance is poor [61] . The 3D framework of Na 3 V 2 (PO 4 ) 3 cathode consists of strongly bonded tetrahedral [PO 4 ] and octahedral [VO 6 ] units with large gaps, favoring fast ion transport.…”
Section: V-based Phosphatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review, we focus on the fabrication and applications of MXenes, MXene‐based, and MXene‐derived materials in different MIBs, from classical LIBs to novel SIBs, PIBs, MgIBs, and AIBs, in particular concerning their roles in electrochemical reactions. [ 30 ] Initially, a brief introduction and overview of the properties of MXenes are presented. Then highlight the recent progress by using MXene‐based materials for different MIBs.…”
Section: Introductionmentioning
confidence: 99%